2014
DOI: 10.1186/1478-811x-12-34
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the mechanism behind Fibroblast Growth Factor (FGF) induced biphasic signal-response profiles

Abstract: BackgroundThe Fibroblast Growth Factor (FGF) pathway is driving various aspects of cellular responses in both normal and malignant cells. One interesting characteristic of this pathway is the biphasic nature of the cellular response to some FGF ligands like FGF2. Specifically, it has been shown that phenotypic behaviors controlled by FGF signaling, like migration and growth, reach maximal levels in response to intermediate concentrations, while high levels of FGF2 elicit weak responses. The mechanisms leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
84
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(96 citation statements)
references
References 48 publications
12
84
0
Order By: Relevance
“…A high concentration of FGF maintained a prolonged ERK1/2 activity, whereas a lower concentration of FGF shortened the activation period of ERK1/2 signaling, inducing cell differentiation or proliferation, respectively [47]. It is not fully understood how these dose-dependent mechanisms function, but it is suggested that competition between binding of the FGF ligand to heparan sulfate glycosaminoglycans and FGF receptors leads to different responses in cells [48]. Nevertheless, it is clear that different FGF concentrations can differentially regulate intracellular signaling and, thus, cellular responses to this growth factor, and that this has important implications for understanding how quantitative and temporal changes in FGF concentrations can influence cell proliferation, migration, survival, and differentiation during embryo development, including the regulation of XY PGC proliferation and/or differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…A high concentration of FGF maintained a prolonged ERK1/2 activity, whereas a lower concentration of FGF shortened the activation period of ERK1/2 signaling, inducing cell differentiation or proliferation, respectively [47]. It is not fully understood how these dose-dependent mechanisms function, but it is suggested that competition between binding of the FGF ligand to heparan sulfate glycosaminoglycans and FGF receptors leads to different responses in cells [48]. Nevertheless, it is clear that different FGF concentrations can differentially regulate intracellular signaling and, thus, cellular responses to this growth factor, and that this has important implications for understanding how quantitative and temporal changes in FGF concentrations can influence cell proliferation, migration, survival, and differentiation during embryo development, including the regulation of XY PGC proliferation and/or differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several multiscale modeling studies have linked PK/PD models with the downstream signaling and cell-surface reactions. 63,64 We can implement a similar approach, combining our model with downstream signaling models [65][66][67] to enable broader application of our model. In addition, anti-angiogenic therapy is usually used in combination with chemotherapy in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…FGFR signaling is complicated by the existence of multiple FGF ligands and the requirement for cell surface heparin sulfate proteoglycans (HSPGs) to stabilize FGF ligand-receptor complexes. A variety of computational models have been developed to study FGF ligand-receptor binding and regulation by HSPGs in vitro 7275 , showing that HSPGs able to form active FGF2-HSPG-FGFR signaling complexes are required for effective downstream signaling 76 . FGF binding to EC receptors and to the vascular basement membrane under physiological flow conditions has also been simulated, both in vivo 77, 78 and in the context of a bioreactor 79, 80 .…”
Section: Microvascular Systems Physiology and Pathologymentioning
confidence: 99%